Strong interaction effects in Σ- atoms - Petridou, Th. (HNPS Advances in Nuclear Physics, 2020)
An approximation is made for the Σ- atomic energy shifts and widths due to strong interaction central and spin-orbit parts of the potential with the use of the S-Matrix Approach, introduced by DelofF. This simplified model is applied in 12C_Σ in connection with the Σ-hypernuclear data: 12C_Σ. It is concluded that there is an essential influence of the strong interaction and especially of the nuclear spin-orbit coupling in the spectra of Σ-12C, mainly for the p-shell.